PENGARUH STARTUP SEBAGAI DIGITALISASI BAGI EKONOMI KREATIF DI INDONESIA - Ermawati, Sri; Lestari, Putri (Transpublika Publisher, 2022)
Startups are very popular in Indonesia. The progress of technological digitalization has had a significant impact on the country's economy through a creative economy supported by the development of startups. This study aims to determine the impact caused by startups as digitalization for the creative economy in Indonesia. This study uses a qualitative descriptive method with the type of library research. The data used is secondary data. The results of this study indicate that the wider development of startups as digitalization is quite large to have a positive influence on the progress of the creative economy in Indonesia by looking at changes in consumer behavior of creative actors using digital technology to start businesses so that they get big profits. Because startups are digital-bound companies, it makes it easier for creative actors to sell products and services.